Totally real submanifolds in a complex projective space - Liu Ximin (International Journal of Mathematics and Mathematical Sciences)
In this paper, we establish the following result: Let M be an n-dimensional complete totally real minimal submanifold immersed in CPn with Ricci curvature bounded from below. Then either M is totally geodesic or inf  r≤(3n+1)(n−2)/3, where r is the scalar curvature of M.